Development of the Role of Higher Education Libraries in Realizing Entrepreneurial University at Sebelas Maret University - Haryanto Haryanto; Dian Hapsari (Proceedings Series on Social Sciences & Humanities, 2023)
This research examines how the development of the role of higher education libraries in realizing Entrepreneurial University at Sebelas Maret University, including creating a dedicated entrepreneurship information center and providing specialized training and support services. This study uses a qualitative method with a descriptive approach, data analysis using the Miles and Huberman approach. Data obtained through observation, interviews and documentation. The research subjects consisted of library leaders, librarians, students and library staff. The study found that developing the role of higher education libraries in realizing entrepreneurial universities through 3 activities, namely entrepreneurial information literacy, coaching clinics and best practices. Information literacy activities in the field of entrepreneurship include: entrepreneurship seminars and workshops. Coaching clinic activities, namely direct dialogue with sources of entrepreneurship practitioners. Meanwhile, best practice is manifested through contests for proposals for entrepreneurial ideas and their implementation. College Libraries are transformed by providing maker space (entrepreneur corner) where students gather to interact and discuss to generate ideas and solve various problems related to entrepreneurship.